Analysis of Collaborative Governance of The Nation's Collective Memory Archive Registration Program - Utami, Yuanita; Madjid, Udaya (UI Scholars Hub, 2025)
Archive Registration as Collective Memory of the Nation is one of the efforts to preserve the documentary heritage of the Indonesian nation. In its implementation, the National Archives of the Republic of Indonesia involves non-governmental institutions, namely state universities and history and culture activists in the nomination, and also involves community organizations, political organizations, and companies in mobilizing participation. This collaborative governance has an impact on the implementation of the Archive Registration as Collective Memory of the Nation program. The research question is how is the implementation of Collaborative Governance in the program and what factors hinder its implementation. The purpose of the study is to implement the application of Collaborative Governance in the Archive Registration as Collective Memory of the Nation Program and to identify the factors that hinder its implementation. The implementation of the program is explained using the theory of Ansell and Gash, namely the initial aspects in the form of successful face-to-face dialogue, building trust, shared understanding, commitment to the process, and intermediate results. This study uses a descriptive research method with a qualitative approach. Researchers collect data using secondary data and review relevant literature on collaborative governance, archiving, and the nation's collective memory. The results of this study indicate that the implementation of Collaborative Governance in the Archives Registration Program as the Nation's Collective Memory has been running well, but needs to be optimized by improving the inhibiting factors in its implementation.